Strengthening Farmers' Capacity for Brown Planthopper Management through Articulate Storyline-based Interactive Digital Extension - Purie Tri Andriani; Gunawan; Lisa Navitasari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Brown planthopper (Nilaparvata lugens) remains one of the most destructive rice pests, necessitating environmentally friendly management supported by effective agricultural extension. This study examined the effects of farmer characteristics and Articulate Storyline-based interactive digital extension on strengthening this capacity for sustainable pest management in Tulungagung Regency, Indonesia. A one-group pretest–posttest pre-experimental design involved 84 rice farmers selected through multistage sampling. Questionnaires were validated (63 of 67 items valid, r-table = 0.361, n = 30) and reliable (Cronbach’s alpha 0.851–0.905). Intervention effectiveness was evaluated using N-Gain analysis, while multiple linear regression with classical assumption testing identified the influencing factors. Farmer characteristics significantly affected the outcome (B = 0.141, standardized ? = 0.150, t = 2.301, p = 0.024), while the digital extension medium showed a substantially greater influence (B = 1.249, standardized ? = 0.866, t = 13.310, p < 0.001). The model explained 69.1% of the variance (adjusted R² = 0.683; F (2,81) = 90.588, p < 0.001), confirming that instructional design outweighs demographic factors in building this capacity for effective pest control. Extension agencies should therefore prioritize content clarity and instructional quality over demographic targeting when developing digital media. As a single-group, one-region study, causal inference and generalizability remain limited; quasi-experimental or multi-region designs are recommended for future research. Overall, the findings highlight Articulate Storyline’s potential as an innovative tool for advancing environmentally friendly brown planthopper control and the broader digital transformation of agricultural extension services. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 4: Quality EducationSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 15: Life on Land